La Responsabilidad Social Corporativa en la empresa SEPRYTSA S.A. - Ron Puente, Jennifer Stephania (2023)
Corporate Social Responsibility (CSR) or Corporate Social Responsibility (CSR) refers to the adoption of policies that promote human development and business management in a sustainable manner in the economic, social and environmental fields. In Ecuador, CSR is a relatively new concept and many companies lack concrete strategies in this regard. However, there is growing interest in implementing CSR practices, as it is recognized that it can provide competitive advantages and improve business development. In the Latacunga canton, some companies are studying its implementation, such as the company SEPRYTSA S.A., which through staff surveys and an interview with the company manager it was obtained that in the social dimension it works under ethical principles and maintains a good relationship with the clients. In the economic dimension, respondents had little knowledge about the economic management of the company, but they highlighted the quality of services and customer satisfaction. Finally, the environmental dimension, the company lacks environmental plans and there is no environmental awareness in the appropriate use of resources. The manager showed good knowledge about social responsibility and expressed her willingness to implement a corporate social responsibility plan in the company. Therefore, a proposal for a company responsibility plan was made focused on its needs.